Real activities management, financial distress and corporate governance: Malaysian evidence / Mojtaba Shayan Nia - Nia, Mojtaba Shayan (Institute of Graduate Studies, UiTM, 2017)
Positive accounting theory predicts that firms approaching deteriorating financial performance may make income-increasing accounting choices. The firms manipulate earnings upward in an attempt to ride out what is probably deemed by the management as a temporary bad period. The primary objective of this thesis is to examine real activities based earnings management among distressed Malaysian firms over the years, covering both prior and after being officially designated as “PN17 firms”. Additionally, the study aims to investigate whether real activities management techniques among distressed Malaysian firms change across time and industries in which the firms operate. The study also aims to examine the moderating effects of corporate governance on real activities management. The study detects real activities manipulation by investigating patterns in cash flow from operations (CFO), discretionary expenses, and production costs. This study uses the Roychowdhury (2006) models to derive the normal level of CFO, discretionary expenses and production costs. Deviations from the normal levels are termed abnormal CFO, abnormal discretionary expenses and abnormal production costs. In addition, a review of the corporate governance literature revealed several attributes that may affect the degree of real activities management, simply because their role in enhancing monitoring mechanism…